Strengthening Al- Islam and Muhammadiyah for Indonesian Citizens in Sanggar Utara Gombak, Kuala Lumpur, Malaysia - Shohib, Muhammad Wildan; Eko Wicaksono; Jihan Salsa Biela; Fitra Hamdani; Nizma Siti Alaina (Abdi Psikonomi, 2025)
Intercultural and interfaith marriages are common occurrences in major cities around the world, including Kuala Lumpur, Malaysia. The problem is that many Indonesian citizens (WNI) and their children lack clear identities and do not receive proper education, especially religious education. This is certainly a phenomenon that deserves attention in ensuring the sustainability of the formation of harmonious, loving, and compassionate families based on Islamic guidance. Therefore, this phenomenon has been responded to by establishing studios that accommodate children who are victims of parents who do not have clear identities. Sanggar Gombak Utara in Kuala Lumpur, Malaysia is one such studio that accommodates children who do not have identities and do not receive proper access to education there. We, through PKM-KI, initiated an activity with the theme “Strengthening Islam and Muhammadiyah for Cross-Cultural Indonesian Families in Sanggar Utara, Kuala Lumpur, Malaysia,” which is a solution we can offer to Indonesian citizens, especially children, in Sanggar Gombak Utara, Kuala Lumpur, Malaysia. The objectives of carrying out this activity include: (1) providing religious education for children at Sanggar Gombak Utara Kuala Lumpur Malaysia, (2) providing a forum and facilities for children to provide counseling guidance in order to develop the interests and talents of children at Sanggar Gombak Utara Kuala Lumpur Malaysia. The implementation method for this service is carried out by providing religious education for children at Sanggar Gombak Utara Kuala Lumpur Malaysia with various activities such as Ceria Study, Koran Study Studio and Islamic Fun Games.